A Rapid Prototyping Technique for Microfluidics with High Robustness and Flexibility - Liu, Zhenhua (Micromachines (Basel), 2016)
In microfluidic device prototyping, master fabrication by traditional photolithography is expensive and time-consuming, especially when the design requires being repeatedly modified to achieve a satisfactory performance. By introducing a high-performance/cost-ratio laser to the traditional soft lithography, this paper describes a flexible and rapid prototyping technique for microfluidics. An ultraviolet (UV) laser directly writes on the photoresist without a photomask, which is suitable for master fabrication. By eliminating the constraints of fixed patterns in the traditional photomask when the masters are made, this prototyping technique gives designers/researchers the convenience to revise or modify their designs iteratively. A device fabricated by this method is tested for particle separation and demonstrates good properties. This technique provides a flexible and rapid solution to fabricating microfluidic devices for non-professionals at relatively low cost.